Identification of Variables Influencing the Mental Health of Pregnant Women - Setyorini, Catur; Ismarwati, Ismarwati; Mamnuah, Mamnuah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Pregnancy is an important period in a woman’s life cycle, which is often associated with changes in emotions and moods. Mental health disorders affect nearly one-fifth of pregnant women during the prenatal and postpartum periods. Some of the mental disorders that are often encountered are depressive disorders, anxiety disorders, psychotic disorders, and post-traumatic stress disorders. Mental health disorders are triggered by the social, economic, and physical environment. Identification of risk factors during pregnancy and early intervention will reduce morbidity in women, prevent postpartum mental disorders, and protect the health of the baby. Objective: This study aims to find out the factors that influence the mental health of pregnant women at Puskesmas (Community Health Center) Polanharjo, Klaten. Research Method: This research performed an analytical survey with a cross-sectional approach. The research sample was 83 pregnant women who made ANC visits at Polanharjo Community Health Center in Klaten. The data collection instruments were a questionnaire on respondent characteristics, the DASS-21 questionnaire, and the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire. The statistical test was conducted by having univariate, bivariate, and multivariate analyses. Results: The mental health of pregnant women at Polanharjo Community Health Center was 75.9% normal and 24.1% abnormal (anxiety). The factors that affected the mental health of pregnant women were education, gravida, social support, and history of pregnancy. Meanwhile, factors such as age, occupation, maternal illness, and planned pregnancy did not affect the mental health of pregnant women. Conclusion: The social support factor is the most influential factor for the mental health of pregnant women at Polanharjo Klaten Polanharjo Community Health Center.